Navigating the Go-Down Zone in Namuwongo: reimagining spaces for informal traders in Kampala - Masuba, Daniel (School of Architecture, Planning and Geomatics, 2023)
Kampala, like many cities in the global south, is experiencing urbanisation at an unprecedented rate. Eight out of ten people are taking up informal employment, many of whom set up and occupy sites within highly contested spaces in the urban realm. Modernist planning and developments across the city are unable to sustain the growing number of traders in the city. The Godown Zone in Namuwongo provides an entry point for a self-organised community of informal traders who have taken upon themselves to create spaces for trade and occupation in a restricted space a few kilometres away from the local market. The Godown Zone offers a range of opportunities for inclusive and sustainable development however it also highlights the urban disconnect between planners need to control functions of spaces and the actual functioning of such spaces. Research has shown a bottom-up design approach through engaging with traders allows for effective and multifunctional development of spaces. This project has therefore development an urban design framework to amplify voices of the trading community of Namuwongo while factoring in long term development plans through interviews, observations, research studies, and site data analysis. By incorporating the experiences of the users, this urban design framework hopes to contribute to the development of an inclusive and vibrant city